Intentions in the experience of meaning - Gibbs, Raymond W. (Cambridge University Press, 1999)
"What do our assumptions about authorship matter for our experience of meaning? This book examines the debates in the humanities and social sciences over whether authorial intentions can, or should, constrain our interpretation of language and art. This volume challenges the traditional idea that intentions exist solely in the minds of individuals, and formulates a new conceptual framework for examining if and when intentions influence the interpretation of meaning. Intentions in the Experience of Meaning presents a clear and concise overview of state-of-the-art research on the role of intentions in meaningful experience in the fields of psychology, linguistics, philosophy, literature, legal theory, art history, and anthropology."--Jacket